Effect of through bond coupling and conformation on the photophysical properties of σ-bridged systems comprising a vinylnaphthalene donor and a dicyanovinyl acceptor - Kurzawa, Jana; Schneider, S.; Büber, Johannes; Gleiter, Rolf; Clark, T. (Physical chemistry, chemical physics, 2004)
The electron transfer kinetics of the donor-bridge-acceptor (D-B-A) compounds investigated is governed by three different effects: polarity of the solvent, change of conformation (especially rotation of the single bond of the vinylnaphthalene moiety) and the p-character of the bridge (bicyclooctane, norbornane, stellane). The expected increase of the rate of electron back transfer with increasing p-character of the bridge orbitals is only clearly seen in medium and very polar solvents (methylene chloride and acetonitrile). In less polar solvent (2-methyl-THF) the temperature dependence of the charge-transfer (CT) fluorescence of the system with the bicyclooctane bridge points to the existence of two emitting CT conformers. Semiempirical MO calculations with configuration interaction reveal that 2 or even 3 (norbornane bridge) local minima exist on the energy surface of the CT state. They differ mainly in the angle of rotation of the single bond mentioned above, but also by deformation of the bridge structure. In non-polar solvent (methylcyclohexane) the fluorescence behaviour becomes even more complex because emission from the CT state(s) and from the locally excited state overlap. The analysis points to an equilibrium between different rotamers on the energy surface of the lowest locally excited state, on the one hand, and of the CT state, on the other hand. Investigations of the compound with the stellane bridge are hampered by significant photodegradation in methylcyclohexane solution.